Bidirectional Role of NLRP3 During Acute and Chronic Cholestatic Liver Injury. Issue 5 (26th March 2021) - Frissen, Mick; Liao, Lijun; Schneider, Kai Markus; Djudjaj, Sonja; Haybaeck, Johannes; Wree, Alexander; Rolle‐Kampczyk, Ulrike; von Bergen, Martin; Latz, Eicke; Boor, Peter; Trautwein, Christian
Abstract : Background and Aims: Cholestatic liver injury leads to cell death and subsequent inflammation and fibrosis. As shown for primary biliary cholangitis (PBC), the mechanisms and circuits between different cell death pathways leading to disease progression are incompletely defined. Common bile duct ligation (BDL) is a well‐established murine model to mimic cholestatic liver injury. Here, we hypothesized that pyroptotic cell death by the Nucleotide‐Binding Domain, Leucine‐Rich‐Containing Family, Pyrin Domain‐Containing‐3 (Nlrp3) inflammasome plays an essential role during human and murine cholestasis. Approach and Results: NLRP3 activation was analyzed in humans with cholestatic liver injury. Wild‐type (WT) and Nlrp3 −/− mice were subjected to BDL for 2 or 28 days. Chronic cholestasis in humans and mice is associated with NLRP3 activation and correlates with disease activity. Acute BDL in Nlrp3‐deficient mice triggered increased inflammation as well as liver injury, associated with stronger apoptotic and necroptotic cell death. In contrast, NLRP3 deletion led to decreased liver injury and inflammation in chronic cholestasis. Moreover, bridging fibrosis was observed in WT, but not in NLRP3 knockout, mice 28 days after BDL. In contrast, lack of NLRP3 expression attenuated kidney injury and fibrosis after acute and chronic BDL. Importantly, administration of MCC950, an NLRP3 small molecule inhibitor, reduced BDL‐induced disease progression in WT mice. Conclusions: NLRP3 activation correlates with disease activity in patients with PBC. NLRP3 has a differential role during acute and chronic cholestatic liver injury in contrast to kidney injury. Disease progression during chronic cholestasis can be targeted through small molecules and thus suggests a potential clinical benefit for humans, attenuating liver and kidney injury.